Evaluation of the Antinociceptive Effect of Maropitant, a Neurokinin-1 Receptor Antagonist, in Cats Undergoing Ovariohysterectomy - Janaina M. X. Corrêa; Priscila C. L. R. Soares; Raquel V. Niella; Brenda A. Costa; Maxuel S. Ferreira; Alex C. Silva Junior; Aline S. Sena; Kátia M. O. R. Sampaio; Elisângela B. Silva; Fabiana L. Silva; Mário S. L. Lavor (Veterinary Medicine International)
Maropitant is a neurokinin-1 (NK1) receptor antagonist that can be used for pain management. The objective of this study was to evaluate the effect of continuous infusion of two doses of maropitant on cardiorespiratory parameters and its postoperative analgesic effect in cats undergoing ovariohysterectomy. Thirty cats were randomly assigned to one of three groups (10 cats each group): the control group (CG) received a continuous infusion of 10 ml/kg/h Ringer’s lactate; GM30 and GM100 first received an intravenous (IV) bolus of 1 mg/kg maropitant; GM30 then received continuous infusion of 30 μg/kg/h maropitant; and GM100 then received continuous infusion of 100 μg/kg/h maropitant. The maropitant was diluted into Ringer’s lactate and the GM30 and GM100 also received fluids intraoperatively. In all groups, premedication included intramuscular injections of morphine and acepromazine, followed by induction with propofol and maintenance with isoflurane. Temperature, heart rate (HR), Doppler blood pressure (DBP), respiratory rate, oxygen saturation, and measuring the end-tidal carbon dioxide and isoflurane were monitored. Postoperative pain was evaluated using a visual analog scale and the UNESP-Botucatu multidimensional composite pain scale in cats; morphine was used for analgesic rescue. During the surgical procedure, cats in GM100 demonstrated lower HR and DBP than those in CG. With regard to the evaluation of postoperative pain, GM100 required the least frequent morphine rescue and less rescue analgesia compared with CG. In conclusion, cats in GM100 maintained lower DBP and HR and required lower analgesic rescue during the postoperative period. The results suggested that animals receiving maropitant bolus (1 mg/kg) plus (100 μg/kg/h) experienced greater postoperative comfort, reflected by the lesser need for analgesic rescue. The use of maropitant in surgical procedures in cats contributes to postoperative comfort.